The Magic Question: A Simple Question Every Leader Dreams of Answering (Audio Book) - Cottrell, David (McGraw-Hill, 2012)
The business leader's toolbox for increasing morale, decreasing turnover, and contributing more than ever to your company's bottom line "What if you could create a culture where everyone is committed to the greater good of the organization? Sound like a pipe dream? David Cottrell will show you the way . . . ." -Ken Blanchard, coauthor of The One Minute Manager and Lead with Luv How can I help? Isn't that the question every leader longs to hear? What if every person on your team consistently asked you, How can I help? What if your team was totally in sync with and committed to achieving your organizations objectives? What if everyone on your team was willing to leave his or her comfort zone and take a risk to help your team win? Impossible? Unrealistic? Pollyanna? No. The team with the best leader usually wins. Sounds simple ... but what does it take to be the best leader? Often what is missing is the understanding of how to lead others toward a common goal. In its simplest form, leadership comes down to answering six key questions that are important to your team. When your teams needs are being met, they will want to ask you The Magic Question : How can I help? If you depend on results from others, this book is for you. It offers a proven method for creating an atmosphere in which employees willingly give discretionary effort. The Magic Question is not about a new leadership strategy. Strategies come and go. What you will learn in is tried and true regardless of the strategic focus of the time, and the principles apply to businesses in every industry, as well as schools, hospitals, churches, even homes. When you hear The Magic Question, you will know you are on your way to better results and to achieving them faster than ever before. Every team asks the questions. Great leaders have the answers. David Cottrell is President and CEO of CornerStone Leadership Institute, one of the nation's largest publishers of management and leadership resources.